Psoralen-cross-linking study of the organization of intracellular adenovirus nucleoprotein complexes. - Wong, M L (1988)
We used the psoralen-cross-linking technique to investigate the structures of adenovirus nucleoprotein complexes during infection. At late times after infection, three types of psoralen cross-linking patterns were observed. A high cross-linking pattern (type I), with about one cross-link in every 10 to 17 base pairs, was found for the newly synthesized and the bulk of the adenovirus late chromatin. Viral templates involved in replication, transcription, and recombination were all found to exhibit this cross-linking pattern. These results suggest that there is no nucleosome-like organization in the unpackaged late adenovirus nucleoprotein complexes. The second type of cross-linking pattern (type II) had a low cross-linking density of about one cross-link in every 700 to 1,000 base pairs. This cross-linking pattern was found to be associated with the viral DNA in the mature virus particles. The sequences at the termini of the virion DNAs, however, were found to have higher cross-linking densities, as shown by electron microscopy. The third type of cross-linking pattern (type III) was composed of a mixture of various proportions of type I and type II patterns in a single molecule. This mixed cross-linking pattern suggests that these molecules are virion assembly intermediates, with viral DNA being partially packaged in the virus particles. The organization of adenovirus nucleoprotein complexes at early times after infection was analyzed by the gel electrophoresis technique following digestion of the DNA with a restriction enzyme that was inhibited by cross-links. Our data suggest that the viral nucleoprotein complexes at early times after infection have accessibility to psoralen cross-linking between the virion DNA and the late viral nucleoprotein complexes. The observed cross-linking density of the early nucleoprotein complex DNA, however, was inconsistent with the nucleosomelike organization suggested by previous investigators.